2005
DOI: 10.1158/1078-0432.ccr-1004-0021
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Cell Sensitization to α Radioimmunotherapy by Doxorubicin or Paclitaxel in Multiple Myeloma Cell Lines

Abstract: Purpose:The purpose of this study was to analyze different mechanisms (cell cycle synchronization, DNA damage, and apoptosis) that might underlie potential synergy between chemotherapy (paclitaxel or doxorubicin) and radioimmunotherapy with a radionuclides. Experimental Design:Three multiple myeloma cell lines (LP1, RMI 8226, and U266) were treated with 213 Bi-radiolabeled B-B4, a monoclonal antibody that recognizes syndecan-1 (CD138) 24 hours after paclitaxel (1nmol/L) or doxorubicin (10 nmol/L) treatment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 29 publications
(22 reference statements)
1
37
0
Order By: Relevance
“…[52][53][54] Studies have shown that doxorubicin causes DNA unwinding and DNA double-strand breaks, which lead to radiosensitization of the tumor cells. [55][56][57] Another possible reason for better therapeutic efficacy with 186 ReDoxil could be due to the increased blood circulation time, which allowed for better accumulation and distribution of the agent in the tumor. 35 Although 186 Re-PEG-liposomes were less effective in the treatment of large solid tumors in this study, they could be potentially used for the treatment of small tumors, as an inverse correlation between tumor size and accumulation of radioactivity has been shown in preclinical 47,48 and clinical studies.…”
Section: -234748mentioning
confidence: 99%
“…[52][53][54] Studies have shown that doxorubicin causes DNA unwinding and DNA double-strand breaks, which lead to radiosensitization of the tumor cells. [55][56][57] Another possible reason for better therapeutic efficacy with 186 ReDoxil could be due to the increased blood circulation time, which allowed for better accumulation and distribution of the agent in the tumor. 35 Although 186 Re-PEG-liposomes were less effective in the treatment of large solid tumors in this study, they could be potentially used for the treatment of small tumors, as an inverse correlation between tumor size and accumulation of radioactivity has been shown in preclinical 47,48 and clinical studies.…”
Section: -234748mentioning
confidence: 99%
“…Colonies were stained and counted under a microscope, with 50 cells as the minimum number to define a surviving colony. The best-fit survival curve was generated according to a linear-quadratic survival model and the mean inactivation dose (area under survival curve) was calculated as described previously (28). The sensitizing enhancement ratio (SER) was defined as SER = mean inactivation dose control irradiation / mean inactivation dose Nutlin-3 + irradiation.…”
Section: Drugtreatmentmentioning
confidence: 99%
“…For cell cycle analysis, cells were stained with propidium iodide and counted with a FACScan (Becton Dickinson) as described previously (28).…”
Section: Drugtreatmentmentioning
confidence: 99%
“…In MM cell lines, Supiot et al demonstrated superior tumor cell killing by anti-CD138 (syndecan-1) B-B4 MAb labeled with bismuth-213 as compared to iodine-131-labeled antibody suggesting that alpha-RIT might be more suitable for treating www.intechopen.com single cell tumors such as MM (Supiot et al, 2002). Besides B-B4, the MAb MA5, which recognizes mucin-1 expressed by both normal and malignant plasma cells, has been coupled to bismuth-213 to target myeloma cells (Couturier et al, 1999;Supiot et al, 2005). In ASCT conditioning regimens, RIT is a good alternative to TBI as it results in less radiotoxicity for normal organ systems and delivers more radiation to tumors as reflected in improved cure rates (Gustavsson et al, 2003).…”
Section: Radioimmunotherapy (Rit)mentioning
confidence: 99%